A Billion Distorted Thoughts: an Exploratory Study of Criminogenic Cognitions Among Men Who Sexually Exploit Children Over the Internet - Paquette, Sarah (International journal of offender therapy and comparative criminology, 2020)
There is evidence that endorsing a higher level of offense-supportive cognitions is associated with contact sexual offending. Such an association assumes the construct of cognitions as unidimensional, thus ignoring the possibility that specific subtypes of cognitions exist and that certain may be criminogenic. To investigate this possibility, this study aimed at examining the associations between criminal behaviors and cognitive themes found in the discourse of men who engage in sexual offenses against children over the Internet. Through the discourse of a sample of 60 men with online child sexual exploitation material and solicitation offenses, a previous study identified eight cognitive themes: Uncontrollability, Nature of harm, Child as sexual being, Child as partner, Dangerous world, Entitlement, Virtual is not real, and Internet is uncontrollable. These themes were not investigated for their criminogenic nature. Thus, in this study, bivariate analyses were used to determine whether these cognitive themes were linked to three indicators of criminal behaviors: the extent of criminal charges, the diversity of offending behaviors, and the nature of contact with victims. Results suggest that, taken as a whole, online sexual offense-supportive cognitions may not be criminogenic. Moreover, only cognitive themes related to antisocial orientation and atypical sexuality were found linked with criminal behaviors, although associations found remain limited. Findings and associated implications are further discussed for research and clinical purposes.